2010
DOI: 10.3340/jkns.2010.47.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Subdural Hematoma due to an Unnoticed Dural Tear during Spine Surgery

Abstract: We report a rare case of intracranial hypotension that was complicated by a subdural hematoma following spine surgery. Intraoperatively, we did not notice any breach of the dura. However, the patient continued to have fluid leakage from the inferior edge of the lumbar incision. During revision surgery, a small dural tear was identified and repaired. It is likely that a small dural tear was overlooked or the dura was weakened during the initial operation and caused a subdural hematoma associated with intracrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…A review of the literature reveals 44 described cases of massive pleura-dural fistula. It can be observed that 77 % of these cases were caused by trauma of varying aetiologies and only two (4.5 %) of the cases were described as subsequent to post-operative thoracic disc resection [2,9,[14][15][16][17]. Recently, two cases of spontaneous thoracic CSF leakage in the presence of thoracic disc hernias were described [18].…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature reveals 44 described cases of massive pleura-dural fistula. It can be observed that 77 % of these cases were caused by trauma of varying aetiologies and only two (4.5 %) of the cases were described as subsequent to post-operative thoracic disc resection [2,9,[14][15][16][17]. Recently, two cases of spontaneous thoracic CSF leakage in the presence of thoracic disc hernias were described [18].…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
“…This results in tension and occlusion of the superior cerebellar bridging veins, which is thought to result in venous infarction and haemorrhage [21,22]. A review of the literature reveals only five cases of confirmed remote subdural haemorrhage subsequent to spinal surgery [16]. Two of these were subsequent to thoracic spinal surgery, while the remainder were associated with lumbar surgery.…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF leakage after a dural tear during spinal surgery may cause intracranial hemorrhage, such as SDH, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] subarachnoid hemorrhage, 24 ,26 or epidural hemorrhage 11 , 12 , 27 alone or concurrently, but only 17 cases of SDH including the present cases have been reported [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] ( Table 1 ). In most cases, a prolonged headache and nausea were the main symptoms, whereas acute disturbance of consciousness beginning within several hours after spinal surgery only occurred in 2 cases.…”
Section: Discussionmentioning
confidence: 82%
“…Many authors propose that CSF hypotension associated with excessive CSF drainage, results in strain on bridging vessels. The result is a SSDH due to intracranial hemorrhage and migration of blood into the spinal subdural space, facilitated by CSF hypovolemia and gravity [20][21][22][23][24][25][26][27][28][29][30][31][32]. This pathophysiology is also cited for SSDH, after incidental durotomy associated with CSF leak [33][34][35].…”
Section: Discussionmentioning
confidence: 99%